PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN: MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Kantor Pusat PT Nindya Karya) - Aditia, Yanuar Chandra; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to analyzing variable influence transformational leadership style, organizational culture and work motivation against employee performance. This study was conducted at head office of PT Nindya Karya. The number of samples was estabilished by 73 respondents with the sample using methods proprtional random sampling. Measurement in questionnaires using likert scale. Methods of analysis data is used path analysis and for test influence mediation researchers used Sobel test. The results of path analysis showing that total influence transformational leadership style against employee performance through work motivation of 0,384. Total influence organizational culture against employee performance through work motivation of 0,429. Then the results showed that transformational leadership style and organizational culture with the motivation to work as a mediating variable (intervening) have positive and significant impact on the employee perfomance with a value of 92.7% effect of 7.3%, while others may be affected by other variables. The result of Sobel test showing that positive effect on transformational leadership style against employee performance through work motivation by results test indicate t value of 2,45. Positive effect on organizational culture against employee performance through work motivation by results test indicate t value of 3,28. Results test with Sobel test showed the t value is greater than t table at 5% level is 1,96.